Doença de Alzheimer: sobrecarga, estresse e qualidade de vida de cuidadores informais - SILVA, Bianca Fernandes (2023)
Alzheimer's disease is characterized by chronic and progressive neurological disorder that presents early clinical losses that include episodic memory loss, difficulty in acquiring new abilities, evolving with impairments in cognitive functions, and may interfere with the individual's professional or social activities, causing stress, overload, doubts and distress in family members. The objective of this work is to investigate the relationship between stress, overload and quality of life of the informal caregiver of people with Alzheimer's disease. The research was carried out in the Brazilian Association of Alzheimer's (ABRAZ-PA), where 9 caregivers were evaluated. To collect the data, were use the Perceived Stress Scale; the Brazilian version of the WHOQOL-Bref and Caregiver Overload Scale (ESC). As a result, it was observed that in relation to the quality of life of caregivers evaluated in this research, 78% of the caregivers presented regular quality of life and 22% presented the level they need to improve within the ESC. When the caregivers overload was evaluated, 55.5% of caregivers presented a moderate level of overload followed by 33.3% who presented moderate to severe overload. It was also observed the presence of stress in the caregivers, where 44.5% represented high stress and 55.5% reduced stress. It is therefore explicit that the care of the elderly with Alzheimer's disease compromises the health of the family caregiver, since the health of these individuals is affected, so that the stress and the overload caused by the care can influence the recognition of their real state of health, thus interfering in their quality of life.